Improving productivity, costs and environmental impact in International Eye Health Services: using the 'Eyefficiency' cataract surgical services auditing tool to assess the value of cataract surgical services. Issue 1 (20th May 2021) - Goel, Hena; Wemyss, Thomas Alan; Harris, Tanya; Steinbach, Ingeborg; Stancliffe, Rachel; Cassels-Brown, Andrew; Thomas, Peter Benjamin Michael; Thiel, Cassandra L
Abstract : Objective: Though one of the most common surgeries, there is limited information on variability of practices in cataract surgeries. 'Eyefficiency' is a cataract surgical services auditing tool to help global units improve their surgical productivity and reduce their costs, waste generation and carbon footprint. The aim of the present research is to identify variability and efficiency opportunities in cataract surgical practices globally. Methods and Analysis: 9 global cataract surgical facilities used the Eyefficiency tool to collect facility-level data (staffing, pathway steps, costs of supplies and energy use), and live time-and-motion data. A point person from each site gathered and reported data on 1 week or 30 consecutive cataract surgeries. Environmental life cycle assessment and descriptive statistics were used to quantify productivity, costs and carbon footprint. The main outcomes were estimates of productivity, costs, greenhouse gas emissions, and solid waste generation per-case at each site. Results: Nine participating sites recorded 475 cataract extractions (a mix of phacoemulsification and manual small incision). Cases per hour ranged from 1.7 to 4.48 at single-bed sites and 1.47 to 4.25 at dual-bed sites. Average per-case expenditures ranged between £31.55 and £399.34, with a majority of costs attributable to medical equipment and supplies. Average solid waste ranged between 0.19 kg and 4.27 kg per phacoemulsification, and greenhouse gases ranged from 41 kg carbon dioxide equivalents (CO2e) to 130 kg CO2e per phacoemulsification. Conclusion: Results demonstrate the global diversity of cataract surgical services and non-clinical metrics. Eyefficiency supports local decision-making for resource efficiency and could help identify regional or global best practices for optimising productivity, costs and environmental impact of cataract surgery.